Debt Covenant, Tax Expense, and Intangible Assets on Transfer Pricing - Sari, Jenny Puspita; Irawati, Wiwit (Jurnal Akuntansi, 2024)
Purpose - Determine and analyze the effect of Debt Covenant, Tax Expense, and Intangible Asset on Transfer Pricing. Design/methodology/approach - This study uses an associative quantitative approach using multiple linear regression analysis and Eviews 9 data analysis tools. This study uses a sample of 11 companies, which was determined based on the purposive sampling method, which is a sample selection with specific criteria. Findings - The results of this study indicate that Debt Covenant, Tax Burden, and Intangible Asset have simultaneous and significant effects on transfer pricing. Partially, Debt Covenant has a negative and significant effect on transfer pricing, Tax Burden and Intangible Asset have no effect on transfer pricing. Research limitations/implications – The research findings prove that there are differences of interest where companies want to increase profits by minimizing tax payments to the government. However, it is better to use methods that have been legalized by the government and do not conflict with tax regulations in force in Indonesia so as not to harm the state treasury which leads to disputes with the Directorate General of Taxes. Keywords: Debt Covenant, Tax Expense, Intangible Asset, Transfer Pricing